2012
DOI: 10.1007/s10753-012-9464-3
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Inflammation and Insulin Resistance in Obstructive Sleep Apnea Patients with Hypertension

Abstract: Hypertension induced by obstructive sleep apnea (OSA) may be multifactorial in origin, and systemic inflammation is one of the major factors. However, OSA patients do not always have the identical probability with hypertension even in patients with the same history and degree of OSA. The aim of this study was to compare the levels of inflammation and insulin resistance in two groups of patients who had the same degree as well as the same long history of OSA, but with/without hypertension. OSA patients (Apnea H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Baseline characteristics of the study participants are detailed in Table 3. …”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Baseline characteristics of the study participants are detailed in Table 3. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, additional studies have also pointed out to other obesity-related metabolic abnormalities that may influence cytokine levels, as is the case of hypertension. Indeed, OSA patients with hypertension show reduced values of IL-10 accompanied by increased levels of TNF- α , IL-6, and CRP with respect to patients without high blood pressure [ 47 ]. Similarly, stroke patients with severe OSA exhibit increased levels of serum IL-6 when they also show hypertension [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation likely plays a major role in the development of hypertension in OSAS. A previous study showed that OSAS patients with hypertension had higher levels of inflammation and insulin resistance than do those without hypertension [ 30 ]. Since systemic inflammation plays an important role in hypertension in OSAS, PLR may have a role in the development of hypertension in OSAS patients.…”
Section: Discussionmentioning
confidence: 99%